Nilai-Nilai Pendidikan Karakter dalam Buku “Saleh Ritual Saleh Sosial” Karya Kh. A. Mustofa Bisri - Muhammad Khoirul Anam; Agus Sutiyono; Ahmad Maghfurin (DIAJAR: Jurnal Pendidikan dan Pembelajaran, 2024)
Character education has always been an important pillar of education in facing various problems. The problem with our education is that we often encounter students who summarize the things they have done, fight, have low respect for parents and teachers, speak impolite words in communication and often use harsh and even dirty words.This study focuses on the values of character education contained in the book "Saleh Ritual Saleh Sosial" by KH. A. Mustofa Bisri. In this study, the author aims to reveal some of the character education values contained in the book. The approach used in this research is a qualitative approach. While the method used is content analysis, a method used to reveal a large text. organized into main summaries.As for the values of character education found, there are seventen values of character education, namely 1) Adil, 2) Dermawan`, 3) Musyawah 4)Tawadhu` 5) Saleh, 6) Manusiawi, 7) Sabar, 8) Syukur, 9)Takwa, 10) Ridha, 11) Guyub, 12) Jejeg, 13) Istiqamah, 14) Iqtishat, 15)Halim, 16) I`tidal, 17) Sak Madyo.